HYANG IWAK - Edi Triharyantoro (BRIN, 1994)
For Javanese people, the empirical realm is considered closely related to the metemperis realm (the supernatural). It is their view that reality is not divided into separate and unrelated fields, but that reality is seen as a whole. Even clearly, Franz Magnis Suseno said that in essence the Javanese do not differentiate between religious attitudes, and social interactions are at the same time an attitude towards nature, as well as attitudes towards nature at the same time have social relevance.